THE RATIO BETWEEN THE FORCES OF FRICTION WINDING AND ROLLING WHEELS OF THE CRANE: EXPERIMENTAL EVALUATION - Radkevych, O. V.; Yakovliev, S. O.; Bondarenko, L. M.; Stepanenko, O. O. (Science and Transport Progress, 2006)
To determine the ratio of flange friction, the article proposes an experimental and analytical method, combining the analytical value for the rolling friction ratio and its experimental value obtained according to the law of oscillations damping in dry friction. The final experimental & analytical formula contains six parameters and permits to judge about their influence on the value of flange pressure upon the rail and to take the measures for its reduction.